2015
DOI: 10.1152/physiolgenomics.00055.2015
|View full text |Cite
|
Sign up to set email alerts
|

Global deletion ofBCATmincreases expression of skeletal muscle genes associated with protein turnover

Abstract: Lynch CJ, Kimball SR, Xu Y, Salzberg AC, Kawasawa YI. Global deletion of BCATm increases expression of skeletal muscle genes associated with protein turnover. Physiol Genomics 47: 569-580, 2015. First published September 8, 2015 doi:10.1152/physiolgenomics.00055.2015.-Consumption of a protein-containing meal by a fasted animal promotes protein accretion in skeletal muscle, in part through leucine stimulation of protein synthesis and indirectly through repression of protein degradation mediated by its metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 92 publications
(85 reference statements)
0
10
1
Order By: Relevance
“…These reactions serve to meet metabolic demands while indirectly stimulating protein synthesis by limiting oxidation of amino acids (e.g., leucine). In spite of the fact that BCAT2 protein levels have been shown to be involved with metabolism and endurance performance ( 50 , 51 ), our results suggest resistance exercise training or different supplementation paradigms do not impact this marker. The BCKDH complex is critical for BCAA metabolism given that it is the rate-limiting enzyme and is the commitment step toward generation of ATP from BCAA catabolism.…”
Section: Discussioncontrasting
confidence: 69%
“…These reactions serve to meet metabolic demands while indirectly stimulating protein synthesis by limiting oxidation of amino acids (e.g., leucine). In spite of the fact that BCAT2 protein levels have been shown to be involved with metabolism and endurance performance ( 50 , 51 ), our results suggest resistance exercise training or different supplementation paradigms do not impact this marker. The BCKDH complex is critical for BCAA metabolism given that it is the rate-limiting enzyme and is the commitment step toward generation of ATP from BCAA catabolism.…”
Section: Discussioncontrasting
confidence: 69%
“…The cDNA libraries were prepared using KAPA Stranded RNA-Seq Kits with RiboErase (Kapa Biosystems). Next generation sequencing was performed in The Penn State College of Medicine Genome Sciences and Bioinformatics Core facility as previously described in Lynch et al (2015) using a HiSeq 2500 sequencer (Illumina). Demultiplexed and quality-filtered mRNA-Seq reads were then aligned to human reference genome (GRCh38) using TopHat (v.2.0.9).…”
Section: Methodsmentioning
confidence: 99%
“…These mice display lower plasma leptin, insulin, and norepinephrine and have a metabolically healthy phenotype with increased glucose disposal, improved glucose tolerance, and enhanced insulin sensitivity (28). Physiologic changes observed in BCAT KO mice were supported by transcriptomics RNA sequencing studies in the skeletal muscle, which showed an up-regulation of the pathways involved in protein synthesis, degradation, and muscle degeneration and a coordinated decrease in the mRNA levels of genes modulating body weight, glycemia, plasma insulin, and lipid signaling (29). Though lack of BCAT presented a favorable metabolic milieu for protection against metabolic syndrome, gastrocnemius muscles of BCATm KO mice had decreased mass and were functionally intolerant of exercise (28).…”
Section: Bcatmentioning
confidence: 99%
“…Exercise intolerance and reduced muscle mass in BCATm KO mouse are likely outcomes of unavailability of gluconeogenic amino acids derived from glucose during exercise, which exacerbates interruptions in the muscle malate-aspartate cycle and lactate flux into pyruvate during the Cori cycle (28). Decreased muscle mass is also a consequence of reduced levels of a-ketoisocaproic acid (KIC), a leucine metabolite, which under conditions of food withdrawal represses protein degradation (29). BCATc…”
Section: Bcatmentioning
confidence: 99%